A weighty dilemma - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Feeding the growing towns of the South is a hefty challenge for ACP countries, already forced to import massive quantities of food at the expense of local production. To limit deficiencies, and the already alarming levels of obesity in many regions, they